Biorefinery of rice husk to obtain functionalized bioactive compounds - Lopretti, Mary Isabel (2019)
The biomass industrialization valorisation of grains and cereals is considered an opportunity for the countries where agro-industrial activity is one of its main economic activities, rendering new higher-value products with a concomitant solution to waste accumulation issues. To that end, in this work we describe and characterise bioactive compounds generation from rice husk by semisolid fermentation, obtained from 500 g of the material at room temperature and 60% humidity with mixed cultures of Phanerochaete chrysosporium and Gloeophyllum trabeum. The extract was evaluated in different situations: murine mammary tumour cells (4T1), normal cells (NIH 3T3) and in Lactobacillus acidophilus, and Trichoderma harzianum. The results exhibited that the extract inhibited 4T1 cells at concentrations higher than 20μg/mL, but did not inhibit normal cells, and displayed germicide activity after 3 days incubations. We propose that these functionalized compounds have a potential application in industry/agriculture/medicine obtained from rice husk waste.